Consideration of Road Management from the View Points of Long- and Short-Distance Road User’s Satisfaction - Wardhana A.P.; Ishibashi K.; Kiyota M. (Civil Engineering Dimension, 2011)
This study observed long- and short-distance road user satisfaction with national road infrastructure in order to direct future road management strategies. The research was a quantitative research method using questionnaire translated into the Japanese Language. The questionnaires were distributed to 2000 road users of two national roads in Saga, Japan. A five-point Likert scale was used to measure road user satisfaction, then the data were analyzed using stepwise regression. Based on regression model, long- and short-distance road user satisfactions were both affected by two same elements (road surface and road facilities). The availability of sidewalks mostly affected short-distance road user satisfaction. On the other hand, the smoothness of road surface was more considered by long-distance road user. Considering the findings, existing problems of inappropriate-infrastructure quality can be addressed to help satisfy user’s expectations.